Examining the influence of intellectuals on commodity speculation. Issue 83 (July 2017) - Field, Sean
Abstract: Global food price volatility began shortly after Gorton and Rouwenhorst (2004, 2006) recognized that commodity index speculation was financially underexploited by institutional investors. Pro-commodity speculation and pro-index speculation arguments were not new, but gained new significance when the US Mortgage and Global Financial crises began to unfold and investors were looking for new places to funnel money. The literature has linked financial speculation by index funds and hedge funds to global food price volatility and the food riots in 2008 and 2011. The literature, however, leaves readers with the perception that index funds and hedge funds alone created the recent wave of commodity futures speculation. This paper argues that a small but important group of intellectuals were vital to the promotion and regulation of commodity speculation by index funds and hedge funds, which has affected the world as a whole.